PENGEMBANGAN TES MATEMATIKA BERBASIS POWERPOINT VISUAL BASIC FOR APPLICATION (VBA) DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA (JURNAL LEMMA, 2018)
This study aims to determine the implications of mathematical tests developed through PowerPoint Visual Basic for Application (VBA) in improving students' mathematical problem-solving abilities. Powerpoint Visual Basic for Application (VBA) is an interactive learning media that is used in learning and is able to display interesting learning and is used to design daily practice questions or evaluation of learning. This study uses the R & D method with data collection techniques used are interviews, validation, and tests. Interviews aim to analyze problems in schools, validation needs to be done for product feasibility tests based on expert teams, while the test aims to determine the product implications that have been developed on mathematical problem-solving abilities. Products are developed based on school needs using Visual Basic for Application (VBA). The results of this study obtained a probability value smaller than t-count (0.050 <2.011) in other words there were significant differences in the mean values between the experimental class and the control class so that PowerPoint tests based on Visual Basic for Application (VBA) had implications for improving ability solving student math problems